Supplement to the revision of the genus Brachelytrium Obenberger, 1923 (Coleoptera: Buprestidae: Buprestinae: Anthaxiini) - Bílý, Svatopluk; Bellamy, Charles L. (Zootaxa, 2010)
Eight new species of the essentially Afrotropical anthaxiine buprestid genus Brachelytrium Obenberger, 1923 are described: Brachelytrium (Brachelytrium) aeneum sp. nov. from South Africa, B. (B.) beninense sp. nov. from Benin, B. (B.) mauritanicum sp. nov. from Mauritania, B. (B.) niehuisi sp. nov. from Namibia, B. (B.) nigrum sp. nov. and B. (B.) purpureiventre sp. nov. from Kenya, B. (Elytrobrachium) caeruleum sp. nov. from Zambia and B. (E.) metallicum sp. nov. from Kenya, Zambia, Zimbabwe. Brachelytrium jemeni Brechtel, 2000 is transferred to the subgenus Elytrobrachium. All new species are illustrated and compared with the most similar species, distinguished in a key to subgenera and species. A complete checklist for the genus is given including all 25 species and two subgenera.